Large institutional experience with dose-intensive chemotherapy and stem cell support in the management of sarcoma patients - Kasper, Bernd; Dietrich, Sascha; Mechtersheimer, Gunhild; Ho, Anthony Dick; Egerer, Gerlinde (Oncology, 2007)
Background: The prognosis of patients with advanced sarcoma remains poor. Whether high-dose chemotherapy with stem cell support improves the long-term outcome for these patients or not is controversial. Methods: We present a large institutional experience of sarcoma patients treated with this therapy option. Thirty-eight patients with bone (n = 17) and soft tissue sarcomas (n = 21) were included. Apart from haematological complications, no WHO grade III-IV complications were observed. One patient died due to cardiac arrest after transplantation. Results: Following chemotherapy and/or surgery, but prior to high-dose chemotherapy, diagnoses were made of: no evidence of disease (NED; n = 12), partial remission (n = 17), stable disease (n = 3) and progressive disease (PD; n = 6). Six patients died within 8 months due to PD, in 18 patients disease recurred and led to death and 13 patients are alive with/without disease. Median progression-free survival was 19.1 months (range: 0-121) for all patients, and 48.8 months (range: 3-121) for 12 patients with NED. Conclusion: A subgroup of patients with NED before high-dose chemotherapy gained survival benefit. Therefore, we emphasize the value of high-dose chemotherapy as a treatment option for younger patients with a good performance status in partial or complete remission.